The African Continental Free Trade Area:: Challenges and Possible Successes - Mlambo, Victor H.; Thusi, Xolani; Zubane, Sphephelo; Mlambo, Daniel N (Latin American Journal of Trade Policy, 2022)
Free trade agreements have been known to have numerous benefits, especially from an economic point of view, however, it has been argued that for them to be successful, they ought to be complemented by a conducive socio-economic –and by extension political environment. Regrettably, the African Continental Free Trade Area agreement (AfCFTA) arrived at a time when Africa was economically and politically unstable; conflict and economic insecurity have exacerbated the lack of development in the contintent. As a result of the above, this paper seeks to understand how African states will navigate their various economic and, by extension, political interests in the hope of contributing to the success of the AfCFTA. Finally, the paper will answer whether Africa is ready for a free trade agreement by employing a qualitative research approach and reviewing current literature.